2017
DOI: 10.1080/02680513.2017.1415140
|View full text |Cite
|
Sign up to set email alerts
|

What factors promote student resilience on a level 1 distance learning module?

Abstract: Resilience is understood to be the ability to adapt positively in the face of adversity. In relation to new students on a distance learning module, this can mean how they adapt and make sense of the demands of their chosen study to enable them to persist in their studies. This article reports a small-scale study involving semistructured telephone interviews with students on a level 1 distance learning module at the UK Open University. Students identified the challenges they experienced such as carving out time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
(17 reference statements)
1
17
0
Order By: Relevance
“…This similarity gave some kind of support that Asian learners regardless of the level of education generally possessed a high level of realistic optimism in learning, one of the characteristics of resilience (Reivich & Shatte, 2002). With this positive attitude, learners would likely have more productive perspectives in handling challenges and overcome adversity (Bronk, 2013;Kim & Kim, 2016;Nguyen et al, 2015;Simons et al, 2018). Next, item number 7, "I have self-discipline" producing a mean score of 3.83 also merited further comments.…”
Section: Learners' Level Of Resilience In Learning English Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…This similarity gave some kind of support that Asian learners regardless of the level of education generally possessed a high level of realistic optimism in learning, one of the characteristics of resilience (Reivich & Shatte, 2002). With this positive attitude, learners would likely have more productive perspectives in handling challenges and overcome adversity (Bronk, 2013;Kim & Kim, 2016;Nguyen et al, 2015;Simons et al, 2018). Next, item number 7, "I have self-discipline" producing a mean score of 3.83 also merited further comments.…”
Section: Learners' Level Of Resilience In Learning English Onlinementioning
confidence: 99%
“…Resilience enables learners to not easily give up and to overcome challenges of learning in the long run. Simons et al (2018) stated that though numerous authors give various definitions of resilience, in general, it is based on two core concepts, which are: adversity and positive adaptations. In short, resilience could be understood as one's ability to positively adapt when facing adversity (Simons et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Further,, Simons, Beaumont, and Holland (2018) explained that there are two core ideas in defining resilience: adversity and positive adaptations. Hence, resilient learners are those who can positively adapt when they are facing adversities (Simons et al, 2018), difficulties of learning online amidst the Covid-19 pandemic being one of them.…”
Section: Introductionmentioning
confidence: 99%
“…Some research showed that students' motivation and learning achievement is low in this course. The difficulty in studying this course encourages the need for innovative learning strategies with a student-centered learning approach (Conradty & Bogner, 2019;Jacobs & Renandya, 2019;Simons, Beaumont, & Holland, 2018;Thuneberg, Salmi, & Bogner, 2018). This innovative learning is supported by the existence of adequate learning resources, one of which is a lecture module.…”
Section: Introductionmentioning
confidence: 99%